Children's thoughts and feelings about their donor and security of attachment to their solo mothers in middle childhood. Issue 4 (10th February 2017) - Zadeh, S.; Jones, C.M.; Basi, T.; Golombok, S.
Abstract: STUDY QUESTION: What is the relationship between children's thoughts and feelings about their donor and their security of attachment to their solo mothers in middle childhood? SUMMARY ANSWER: Children with higher levels of secure–autonomous attachment to their mothers were more likely to have positive perceptions of the donor, and those with higher levels of insecure–disorganized attachment to their mothers were more likely to perceive him negatively. WHAT IS KNOWN ALREADY: There is limited understanding of the factors that contribute to children's thoughts and feelings about their donor in solo mother families. In adolescence, an association was found between adolescents' curiosity about donor conception and their security of attachment to their mothers. STUDY DESIGN, SIZE, DURATION: 19 children were administered the Friends and Family Interview and Donor Conception Interview between December 2015 and March 2016 as part of the second phase of a longitudinal, multi-method, multi-informant study of solo mother families. PARTICIPANTS/MATERIALS, SETTING, METHODS: All children were aged between 7 and 13 years and had been conceived by donor insemination to solo mothers. Interviews were conducted in participants' homes. The Friends and Family Interview was rated according to a standardized coding scheme designed to measure security of attachment in terms of secure–autonomous, insecure–dismissing, insecure–preoccupied and insecure–disorganized attachment patterns. Quantitative analyses of the Donor Conception Interview yielded two factors: interest in the donor and perceptions of the donor. Qualitative analyses of the Donor Conception Interview were conducted using qualitative content analysis and thematic analysis. MAIN RESULTS AND THE ROLE OF CHANCE: Statistically significant associations were found between the perception of the donor scale and the secure–autonomous and insecure–disorganized attachment ratings. Children with higher levels of secure–autonomous attachment to their mothers were more likely to have positive perceptions of the donor ( r = 0.549, P = 0.015), and those with higher levels of insecure–disorganized attachment to their mothers were more likely to perceive him negatively ( r = −0.632, P = 0.004). Children's narratives about the donor depicted him as a stranger ( n = 8), a biological father ( n = 4), a social parent ( n = 3), or in ambivalent terms ( n = 4). LIMITATIONS, REASONS FOR CAUTION: Findings are limited by the wide age range of children within a small overall sample size. Participants were those willing and able to take part in research on donor conception families. The statistical significance of correlation coefficients was not corrected for multiple comparisons. WIDER IMPLICATIONS OF THE FINDINGS: Findings highlight the importance of situating children's ideas about the donor within family contexts. It is recommended that those working with donor conception families consider this when advising parents about whether, what and how to tell children about donor conception. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by the Wellcome Trust [097857/Z/11/Z]. The authors have no conflicts of interest to declare.